Anne Rebecca Daoma: From Freed Slave in Southern Malawi to an Anglican Missionary' at the Cape Colony, 1863-1931 - Mbaya, Henry (Exchange, 2019)
This article outlines the progressive journey of Anne Rebecca Daoma in the Anglican Mission at the Cape in the years 1863 to 1936. Daoma was the first African woman from Central Africa, to be trained by the Anglican missionaries in South Africa. The article traces the life of Daoma, a Yao, from the moment when the Universities Mission to Central Africa (UMCA) missionaries set her free from the slave trade in Southern Malawi in 1861, and through some phases of her life at the Cape as a missionary and argues that colonial missionary life and culture fashioned her in becoming Anne Rebecca Daoma'.